DESIGN AND CONTROL OF BIOMIMICRY EYE USING SOFT ACTUATOR - Hong Win Soon; Nenny Ruthfalydia Rosli; Ahmad Athif Mohd Faudzi (PERINTIS eJournal, 2021)
The purpose of this study is to investigate and implement biomimicry of the human eye through a 3D printed robotic eye and thin McKibben actuators. The human visual system is important and integral to the survival and evolution of humanity. Thus, we look to it for inspiration in designing a robotic visual system that can be adapted into soft robotic systems. This study proposes an improved method in the design of a 3D printed robotic eye which has two Degrees of freedom. The solution is based on the advantage gained through the implementation of the thin McKibben actuators, with a simpler design of the robotic eye as well as 3D printing to produce a robotic structure which can be quickly design, fabricated and deployed. The approach has several notable merits, namely a reduction in design complexity, reduction in size with 2 degrees of freedom. A comprehensive verification via experimentation was carried out to determine the effectiveness of the concept and design. From the experimentation works, it was found that the 3D printed robotic eye can be actuated via the Thin McKibben actuator with an angular movement of around 40 degrees and with 2 Degrees of Freedom. The result shows that the method shows an improvement to currently pneumatically actuated robotic eye with an increase of 33% more angular movement freedom that can be actuated with 2 Degrees of Freedom as well as small compact design. The method proposed in this paper can be implemented in other types of soft robots as well.